Trust in the EU: The Case of Croatia 1995 - 2003 - Štulhofer, Aleksandar; Rimac, Ivan; Landripet, Ivan (2005)
The paper offers an empirical analysis of the dynamics and correlates of trust in the EU in Croatia during the 1995-2003 period. The authors use data from three studies carried out on national probability samples (World Values Survey – Croatia 1995, European Values Survey – Croatia 1999, and the South East European Social Survey Project, 2003) to separate structural (human capital, social capital, standard of living) from situational predictors of local trust in the EU. The findings point out the importance of both.
ENG